“It is better to die”: experiences of traditional health practitioners within the HIV treatment as prevention trial communities in rural South Africa (ANRS 12249 TasP trial) - (:unkn) unknown (My University, 2016)
The ANRS 12249 Treatment-as-Prevention (TasP) cluster-randomized trial in rural South Africa uses a test and treat approach. Home-based testing services and antiretroviral treatment initiation satellite clinics were implemented in every cluster as part of the trial. A social science research agenda was nested within TasP with the aim of understanding the social, economic and contextual factors that affect individuals, households, communities and health systems with respect to TasP. Considering the rural nature of the trial setting, we sought to understand community perceptions and experiences of the TasP Trial interventions as seen through the eyes of traditional health practitioners (THPs). A qualitative study design was adopted using four repeat focus group discussions conducted with nine THPs, combined with community walks and photo-voice techniques, over a period of 18 months. A descriptive, interpretive and explanatory approach to analysis was adopted. Findings indicate that THPs engaged with the home-based testing services and HIV clinics established for TasP. Specifically, home-based testing services were perceived as relatively successful in increasing access to HIV testing. A major gap observed by THPs was linkage to HIV clinics. Most of their clients, and some of the THPs themselves, found it difficult to use HIV clinics due to fear of labelling, stigma and discrimination, and the ensuing personal implications of unsolicited disclosure. On the one hand, a growing number of patients diagnosed with HIV have found sanctuary with THPs as alternatives to clinics. On the other hand, THPs in turn have been struggling to channel patients suspected of HIV into clinics through referrals. Therefore, acceptability of the TasP test and treat approach by THPs is a major boost to the intervention, but further success can be achieved through strengthened ties with communities to combat stigma and effectively link patients into HIV care, including partnership
Keywords: African Research